1996
DOI: 10.1002/j.2168-9830.1996.tb00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Freshman Enrollments: Critical and Non‐critical Factors

Abstract: Freshman enrollment and bachelors degree data over the last three decades for all undergraduates as well as engineering students are analyzed and compared to variations in the numbers of high school graduates. Engineering enrollment data trends are shown to differ significantly from those of undergraduates as a whole and to exhibit little correlation with trends in high school graduation data. Freshman engineering enrollments show a very strong correlation with factors which might indicate to high school stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Table 2 details the specific types of information that are disseminated through these materials. Materials must be informative and geared toward a HS audience (Heckel 1996). We have found that HS students find the thought of working for trendy, popular companies appealing.…”
Section: Preparation Of Materialsmentioning
confidence: 98%
See 4 more Smart Citations
“…Table 2 details the specific types of information that are disseminated through these materials. Materials must be informative and geared toward a HS audience (Heckel 1996). We have found that HS students find the thought of working for trendy, popular companies appealing.…”
Section: Preparation Of Materialsmentioning
confidence: 98%
“…Care is taken to avoid dwelling strictly on traditional and longstanding organizations that may sound boring to this younger audience. Heckel (1996) notes that it is important to link the hard work associated with an engineering degree to the economic rewards of the future. In addition, prospective students want to hear about the fun aspects of college life, such as sporting events, social organizations and dormitory life.…”
Section: Preparation Of Materialsmentioning
confidence: 98%
See 3 more Smart Citations